The atrial fibrillation burden during the blanking period is predictive of time to recurrence after catheter ablation - Cunha, Pedro (2022)
© 2022 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/)